Investigation on the centre of pressure migration for different wing configurations - A Pua’at, Afifi; Zhahir, Amzari; Abdul Hamid, Mohd Faisal; Gires, Ezanee; Ahmad, Mohamed Tarmizi; Hassan, Aziz (Airiti Library, 2022)
A wing-in-ground effect (WIG) craft experiences longitudinal instability due to its center of pressure (COP) location migrating when in transition from in-ground-effect (IGE) to out-of-ground effect (OGE) zone. The study on this subject has always been a grey area and only very limited published research = is available. As an attempt to further support the development of WIG crafts, this study investigates COP migration for different wing configurations using CFD software. It is taken that a satisfying configuration must have a minimal COP migration in term of the vertical height as percentage of chord (HC) and angle of attack (AOA) increment. The significant severances of ground effect depend on the total COP migration from 0◦ to 10°. With this notion, the cases of rectangular and inverse delta wing configurations have been simulated and analyzed using two different airfoil profiles: Clark Y and DHMTU. The COP for each configuration is plotted and based on the analysis results, it is found the COP migration is relatively higher for the rectangular wing configurations that the inverse delta wing configurations. The lowest COP migration is for the inverse delta wing with DHMTU airfoil while the highest migration is for the rectangular wing with DHMTU airfoil.